Integrating Overall Water Splitting with Advanced Oxidation for Wastewater Treatment Using a Bifunctional Medium-Entropy Amorphous Alloy - Cui, Yifan; Wang, Yonghui; Li, Bo; Huang, Jiaqi; Bo, Le; Liu, Hengqi; Mathe, Mahlanyane Kenneth; Samadiy, Murodjon; Guo, Shengfeng; Shen, Hongxian; Sun, Jianfei; Jiang, Sida (Nano-Micro Letters, 2026)
Hydrogen energy is regarded as a clean and reliable approach for storing intermittent energy sources. However, stringent water quality requirements remain critical challenges. The development of a bifunctional catalyst capable of simultaneously driving overall water splitting and degrading pollutants in wastewater can substantially enhance energy utilization efficiency and enable resource recycling. Nevertheless, the mismatch in the optimal pH conditions and the difficulty in balancing degradation efficiency and electrolysis performance remain notable obstacles. In this study, (FeCoNi)80B20 medium-entropy amorphous alloy (MEAA) fibers were prepared using a low-cost melt-extraction method. Owing to the crystalline–amorphous heterostructure, the fibers achieved complete decolorization within 90 s, while remaining effective across a wide pH range. In addition, the (FeCoNi)80B20 delivered overpotentials of 275 and 220 mV for the oxygen evolution reaction and hydrogen evolution reaction, respectively. By synchronizing both catalytic reactions, the (FeCoNi)80B20 enabled direct water splitting in reclaimed water, achieving complete decolorization while preserving electrocatalytic stability in an anion-exchange-membrane electrolyzer for 100 h under highly alkaline conditions (pH = 13.6). Moderate OH* adsorption endowed (FeCoNi)80B20 with excellent ability. This bifunctional catalyst addresses the coupled challenges of energy storage and water scarcity and offers a promising foundation for industrial implementation. Highlights: 1 (FeCoNi)80B20 fibers were prepared via a melt-extraction method with a high cooling rate to construct a crystalline–amorphous heterostructure. A substantial quantity of fibers (~ 100 g) was produced in a single batch, resulting in a competitive cost of approximately 0.51 USD per gram with accurate composition and high quality. 2 In simulated reclaimed water, complete decolorization of the solution was achieved within 60 min, whereas the water splitting process maintained stable operation for approximately 115 h. The total organic carbon removal rate reached 63.24%.